ASP.NET MVC 4 Recipes A Problem-Solution Approach - Ciliberti, John.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
ASP.NET MVC 4 Recipes is a practical guide for developers creating modern web applications, cutting through the complexities of ASP.NET, jQuery, Knockout.js and HTML 5 to provide straightforward solutions to common web development problems using proven methods based on best practices. The problem-solution approach gets you in, out, and back to work quickly while deepening your understanding of the underlying platform and how to develop with it. Author John Ciliberti guides you through the framework and development tools, presenting typical challenges, along with code solutions and clear, concise explanations, to accelerate application development. Inside you will find recipes dealing with streamlined syntax, full control over HTML, a simple API for creating RESTful web services, writing support for test driven development, and more. Solve problems immediately by pasting in code from the recipes, or put multiple recipe solutions together to overcome challenging development obstacles. Dive head first into ASP.NET MVC web development with ASP.NET MVC 4 Recipes.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems